2018
DOI: 10.3164/jcbn.17-117
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic <i>Lactobacillus casei Shirota</i> improves efficacy of amoxicillin-sulbactam against childhood fast breathing pneumonia in a randomized placebo-controlled double blind clinical study

Abstract: The aim of the present study was to investigate the efficacy of oral administration of probiotic Lactobacillus casei Shirota and amoxicillin-sulbactam in treating childhood fast breathing pneumonia. 518 children diagnosed of fast breathing pneumonia were enrolled and randomly assigned to be administered either amoxicillin-sulbactam + Lactobacillus casei Shirota or amoxicillin-sulbactam + placebo. Primary outcome was defined as treatment failure before day 3, and secondary outcome was defined as treatment failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Also, L. shirota has evidence of safe consumption with numerous health benefits and its immune modulating properties thus improving the efficiency of amoxicillin sulbactam in treatment. In conclusion L. shirota can be used as an adjuvant for further treatment (Li et al 2018). The result showed a reduction in the biotoxicity of CFX and CPR, when looking into their degradation products.…”
Section: Shirota Improves Efficacy Of Amoxicillin Sulbactammentioning
confidence: 77%
“…Also, L. shirota has evidence of safe consumption with numerous health benefits and its immune modulating properties thus improving the efficiency of amoxicillin sulbactam in treatment. In conclusion L. shirota can be used as an adjuvant for further treatment (Li et al 2018). The result showed a reduction in the biotoxicity of CFX and CPR, when looking into their degradation products.…”
Section: Shirota Improves Efficacy Of Amoxicillin Sulbactammentioning
confidence: 77%
“…12 Though phototherapy is in practice for more than 50 years, its complications predominantly hypocalcemia put a limit to its prolonged use 12,13 . Therefore measures which can reduce the length of phototherapy are hot focus of research [4][5][6][7] . Recent studies claimed that probiotics supplementation of jaundiced neonates significantly reduced the mean duration of phototherapy and advocated its preferred use in future practice 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, probiotics has gained much popularity 3 and their clinical use has seen a significant rise where there are reports of their benefit in patients with acute and chronic diarrhea 4 and pneumonia. 5 There has been studies investigating their role in the clinical management of neonates with hyperbilirubinemia 6,7 but with controversial results. [8][9][10] Torkaman et al 8 (2017) reported that mean duration of phototherapy was significantly shorter in neonates receiving probiotics in addition to phototherapy as compared to neonates receiving phototherapy alone (3.13±0.70 vs. 3.55±0.74 days; p-value<0.001) in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Antiinflammatory activity in the lungs plays a role in decreasing lung inflammation such as decreasing the levels of proinflammatory cytokines and C-reactive protein (CRP). 27 Probiotic bacteria produce metabolites in the form of short-chain fatty acids (SCFA) consisting of acetate, propionate, and butyrate which are widely present in the colon epithelium. Parts of the butyrate are used as energy by the colonocytes while the rest of the other SCFA are absorbed into the portal circulation through the intestine.…”
Section: Potential Health Effects Of Probioticsmentioning
confidence: 99%